The Evidence for Allogeneic Hematopoietic Stem Cell Transplantation for Congenital Neutrophil Disorders: A Comprehensive Review by the Inborn Errors Working Party Group of the EBMT - Bakhtiar, Shahrzad; Shadur, Bella; Stepensky, Polina (Frontiers in Pediatrics, 2019)
Congenital disorders of the immune system affecting maturation and/or function of phagocytic leucocytes can result in severe infectious and inflammatory complications with high mortality and morbidity. Further complications include progression to MDS/AML in some cases. Allogeneic stem cell transplantation is the only curative treatment for most patients with these diseases. In this review, we provide a detailed update on indications and outcomes of alloHSCT for congenital neutrophil disorders, based on data from the available literature.